2014
DOI: 10.1037/a0033228
|View full text |Cite
|
Sign up to set email alerts
|

Rapid guidance of visual search by object categories.

Abstract: Visual search is often controlled by attentional templates that represent specific target items or target features, but can also be directed toward object categories. We studied the relationship between item-based and category-guided attentional control during visual search for one specific item (e.g., the letter C), two or three items (e.g., the letters C, F, and X), or categorically defined targets (e.g., any letter). To assess the efficiency of visual search for single, multiple, or category-defined targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 33 publications
10
77
1
Order By: Relevance
“…Previous electrophysiological studies (Wu et al, 2013;Nako et al, 2014aNako et al, , 2014b have shown that reliable N2pc components are elicited during the selection of search targets that are defined by their category, demonstrating that category-based attentional control processes can operate at relatively early visual-perceptual processing stages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous electrophysiological studies (Wu et al, 2013;Nako et al, 2014aNako et al, , 2014b have shown that reliable N2pc components are elicited during the selection of search targets that are defined by their category, demonstrating that category-based attentional control processes can operate at relatively early visual-perceptual processing stages.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that when the deployment of attention has to be guided by search templates for object categories, target objects can still be selected rapidly, at relatively early stages during the processing of visual input. Importantly, when observers searched for a particular item, nontarget objects that matched the category of the current target (e.g., the letter A during search for the letter P) also triggered N2pc components (Nako et al, 2014a). Although this "foil" N2pc was smaller than the N2pc to targets, it was already reliably present during the 180-200 ms post-stimulus interval.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Target detection is strongly impaired when targets are immediately replaced by another visual stimulus, and therefore can no longer be addressed by recurrent feedback signals. The existence of fast recurrent pathways from categoryselective areas to visual cortex [85] can also explain why category-guided object selection is often remarkably rapid [89]. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 candidate target objects at particular locations in the visual field can be effectively routed back to spatially corresponding regions of visual cortex [18].…”
Section: Box 2: the Role Of Recurrent Feedback Processes In Visual Sementioning
confidence: 99%